The Circular Chromatic Index of Flower Snarks - Ghebleh, Mohammad; Král’, Daniel; Norine, Serguei; Thomas, Robin (The Electronic Journal of Combinatorics, 2006)
We determine the circular chromatic index of flower snarks, by showing that χ’_c(F_3)=7/2, χ’_c(F_5)=17/5 and χ’_c(F_k)=10/3 for every odd integer k7, where F_k denotes the flower snark on 4k vertices.